A Sustainable Financial Accountability and Governance Model for Pesantren: Integrating Business, Education, and Da'wah for Economic Independence - Hoirul Ichfan; Supriyanto (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam syarifuddin Lumajang, 2026)
Pesantren play a strategic role as Islamic educational institutions that function not only as centers for the transmission of religious knowledge but also as agents of da’wah, social empowerment, and community economic development. The complexity of these functions requires accountability and financial governance systems capable of supporting institutional sustainability in a comprehensive manner. This study aims to develop a sustainable pesantren financial accountability and governance model that integrates business, education, and da’wah functions to foster economic independence. The study employed a qualitative approach with a conceptual design through a literature review supported by empirical data collected through interviews, observations, and documentation at Kyai Syarifuddin Islamic Boarding School. The analysis was conducted through the synthesis of theories on accountability, organizational governance, sustainability, Islamic accounting, and pesantren management. The findings indicate that pesantren sustainability is determined by the synergy of three main pillars: business as a driver of economic independence, education as the core value, and da’wah as a source of social legitimacy. This study proposes an Input–Process–Output–Outcome (IPOO)-based Sustainable Pesantren Financial Accountability and Governance Model that integrates organizational resources, financial governance, accountability, business, education, and da’wah. The model contributes to enhancing transparency, stakeholder trust, economic independence, and the long-term sustainability of pesantren.